Perceptions of students on artificial intelligence-generated content avatar utilization in learning management system - Saw Fen Tan (AAOU Journal)
Purpose – This study aims to explore students’ perceptions of the use of an artificial intelligence-generated content avatar (AIGC avatar) within a learning management system (LMS). Design/methodology/approach – This qualitative research involved seven postgraduate students. Data were collected through individual, in-depth interviews. The videos of the AIGC avatar, created using Leonardo, ChatGPT and Heygen, were uploaded to the LMS to communicate with students for the purposes of a welcome note, assignment guide, assignment feedback, tutorial reminders and preparation as well as to provide encouragement and study tips. Students were interviewed at the end of the semester. Findings – The findings of this study indicated that the majority of participating students held positive perceptions regarding the use of the AIGC avatar in the LMS. They reported that it enhanced their perceived instructor’s social presence and motivation to learn. The assignment guide and feedback were particularly valued by the participants. While some students noted the AIGC avatar’s lack of naturalness, others appreciated the clear and professional speech it delivered. Research limitations/implications – The study was confined to seven students from a single course at one institution, which may limit the generalizability of the findings. Future research could involve a larger and more diverse group of participants. Practical implications – The findings may offer education providers an alternative solution for engaging students in an LMS. Originality/value – This study highlights the potential of AIGC avatars to replace text-based communication in LMS and enhance students’ perceived instructor social presence.